Analisis Penerapan Fungsi Agenda Setting pada Konten “Fakta Unik” FTNews di Platform Facebook - Andinilah, Andinilah; Rahmawati, Citra; Nurlatifah, Sopia; Siti Mahmudah Noorhayati; Hakim, Hari (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study analyzes the application of agenda-setting function in FTNews' "Unique Facts" content on Facebook platform within the context of digital media transformation. Employing a qualitative approach with case study method, this research explores how digital media performs agenda-setting function through strategically packaged light content. Data were collected through content observation, audience interaction analysis, and in-depth interviews with FTNews editorial team, then analyzed using Miles, Huberman, and Saldana's interactive analysis model. The findings reveal that FTNews implements three main strategies: (1) selective content curation and packaging focusing on informative value and audience relevance, (2) distribution strategy based on optimal timing and interactive captions leveraging platform algorithmic logic, and (3) micro public agenda formation through active audience participation. The findings confirm that agenda setting in the digital era is collaborative and cyclical, involving dynamic interaction among editorial strategy, audience participation, and algorithmic mechanisms. This study expands agenda-setting theory by demonstrating that light content can effectively shape public agenda through networked agenda-setting process, where audiences act as active agents in agenda formation and reinforcement.